Sustainability in times of pandemic: an analysis today for a new way of doing tomorrow (Research, Society and Development, 2022)
Sustainability in times of pandemic: an analysis today for a new way of doing tomorrow conveys an epistemological and conceptual analysis of Sustainability, contemplating its different operating environments, from the initial ideas, to this unique moment in human history: the pandemic caused by Covid-19. The issues are part of the redefinition of Sustainability in the context of a pandemic, where some environmental aspects benefited from social isolation, such as air, water, rivers and oceans; but on the other hand, one of the main consequences was the issue of garbage that, no longer being produced in the street, in schools and universities, in restaurants, accumulated in homes, forming a major environmental and social problem. For companies, this moment of pandemic is established as an opportune moment to add new values ​​and impact with services and products, as long as they use effective strategies to contain the waste produced. Finally, the universe of urgent and necessary actions in order to have and guarantee a sustainable life, in its broadest concept, covering all dimensions of human life, seem to have been born or acquired consistency with the so devastating health crisis of Covid-19, as all of humanity, consciously or unconsciously, are changing habits and behaviors, seeking strategies for a better quality of life and thus promoting the sustainability of the Planet for them for future generations.